2013
DOI: 10.1057/jdg.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Swedish and Dutch listed companies’ compliance with IAS 36 paragraph 134

Abstract: This article investigates the extent to which companies listed on the Nasdaq OMX (NOMX) and the Euronext Amsterdam (EA), in their 2005 and 2008 annual reports, complied with the disclosure requirements in IAS 36 paragraph 134, as well as the factors that explain why some companies complied with the standard to a higher extent than did other ones. Swedish and Dutch listed companies are chosen as the accounting oversight system differs between the countries. The relationship between the dependent variable, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 72 publications
(114 reference statements)
5
15
0
Order By: Relevance
“…Similar results are contained in the paper of Hartwig (2012) that has found that the compliance level of goodwill's disclosure for Swedish and Dutch listed companies is low, registering an increase over the time covered by the analysis.…”
Section: Literature Reviewsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results are contained in the paper of Hartwig (2012) that has found that the compliance level of goodwill's disclosure for Swedish and Dutch listed companies is low, registering an increase over the time covered by the analysis.…”
Section: Literature Reviewsupporting
confidence: 81%
“…According to previous contributions (Carlin & Finch, 2010;Hartwig, 2012;Devalle & Rizzato, 2012;Petersen & Plenborg, 2010;Teodori & Veneziani, 2010;Biancone, 2012) expect that, in the Italian scenario, there is a lack of compliance both with the requirements of IAS 36 and with Italian public Authorities and Italian Standard Setter. The critical aspects could be related to the quality and precision of the information presented in relation to impairment assumptions and testing procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, D'Arcy et Arca (2018) analyze and summarize the current research about goodwill recognition, impairment and disclosure. Overall, they documented substantial evidence of noncompliance related to the disclosure both for cross-country studies (Glaum, Schmidt, Street & Vogel, 2013;Hartwig, 2015;Mazzi, André , Dionysiou & Tsalavoutas, 2017) and single country studies (Bepari, Rahman & Mollik, 2014;Devalle, Rizzato & Busso, 2016).Given those previous contributions, our second hypothesis tested is:…”
Section: Summary Of Previous Researchmentioning
confidence: 90%
“…For example, an investigation of goodwill disclosure practices among 287 Australian listed firms from 2005-2010 by Guthrie and Pang (2013) showed that the level of compliance with the disclosure requirements to allocate goodwill to cash-generating units increased from 61% in 2005 to 80% in 2010. Likewise, the examination of the disclosure requirements of paragraph 134 of IAS 36 among 472 Dutch and Swedish listed firms for 2005 and 2008 by Hartwig (2015) showed an improvement in the compliance levels over time from an average of 52.7% in 2005 to 61.9% in 2008.…”
Section: Proposed Solutions Offered By Stakeholdersmentioning
confidence: 98%
“…Another shortcoming in the application of an impairment model, as argued by prior studies, is managerial discretions associated with the impairment testing of goodwill (Ramanna, 2008;Chambers and Finger, 2011;Ramanna and Watts, 2012;Hartwig, 2015). Managerial discretions that are frequently discussed in the literature include identification of cash-generating units to which goodwill is allocated (Ernst and Young, 2007;AbuGhazaleh et al , 2011;Abdul Majid, 2013), estimations of fair value of the reporting units containing goodwill (Ramanna, 2008;Chambers and Finger, 2011;Ramanna and Watts, 2012;Li and Sloan, 2017) and determination of discount rates in the estimation of value in use (AbuGhazaleh et al, 2011;ASBJ et al 2014;IFRS Foundation, 2015).…”
Section: Causes Of the Debatesmentioning
confidence: 99%